1994
DOI: 10.1177/002246699402800203
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Employment Inequality among Females with Disabilities

Abstract: Women consistently earn less than men. This holds true for individuals with and without disabilities. Women with disabilities, however, have more negative employment experiences than do men with disabilities. The purpose of this article is to explore the less than desirable conditions that women with disabilities face in employment.Studies dealing primarily with the employment outcomes of females and males with disabilities are reviewed, followed by recommendations for the field of special education. We sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 12 publications
2
16
0
1
Order By: Relevance
“…Evidence suggests that the disadvantages young women with disabilities experience out of school have their roots in the inadequate or inappropriate services they receive while they are in school (Benz & Halpern, 1993;Fulton & Sabornie, 1994;Wagner, 1992). For example, Wagner (1992) found that young women were less likely than males to be involved in occupationally-specific vocational training during high school, and when involved, they were more likely to receive training for sex-stereotyped jobs that rarely pay well (e.g., food service, office occupations).…”
mentioning
confidence: 99%
“…Evidence suggests that the disadvantages young women with disabilities experience out of school have their roots in the inadequate or inappropriate services they receive while they are in school (Benz & Halpern, 1993;Fulton & Sabornie, 1994;Wagner, 1992). For example, Wagner (1992) found that young women were less likely than males to be involved in occupationally-specific vocational training during high school, and when involved, they were more likely to receive training for sex-stereotyped jobs that rarely pay well (e.g., food service, office occupations).…”
mentioning
confidence: 99%
“…Table 2 summarizes findings from both national and selected state follow-up/follow-along studies conducted since 1983. Like the recent work of Fulton and Sabornie (1994), these studies reported findings across various highincidence disability groups and are well recognized by the field for their value in yielding insight into the transition patterns of young adults with disabilities. Levine and Edgar's (1995) study, which runs counter to previous findings (including their earlier analysis oftheir own work), found few significant gender differences in postschool outcomes for youth with learning disabilities, mild mental retardation, and for young adults without disabilities.…”
Section: Table I Women and Jobs: Facts About The Labor Market And Edmentioning
confidence: 71%
“…As our nation swiftly approaches the twenty-first century, it is unfortunate that gender differences continue to plague educational and employment outcomes (Fulton & Sabornie, 1994). Because participation of both men and women in the labor force is positively related to educational attainment, it is essential to examine the indicators of relative performance between the sexes (Mincer, 1990).…”
mentioning
confidence: 99%
“…Furthermore, access to adult service agencies such state vocational rehabilitation agencies provides young adults with knowledge of their rights and responsibilities as employees with disabilities (cultural capital) as well as introduction into networks (social capital) of service providers (Agran, Cain, & Cavin, 2002). Evidence supports that access to adult agencies and vocational experiences are limited by racial/ethnic (Giesen, Cavenaugh, & Sansing, 2004), disability (Gregg, Scott, & McPeek, 1999), and gender (Fulton & Sabornie, 1994) biases. Research can illuminate factors that facilitate and inhibit access to resources of cultural and social capital that potentially increase employment and mitigate marginalization through biases.…”
Section: Using Capital Theory To Informmentioning
confidence: 99%